POLITENESS STRATEGIES IN DIGITAL CODE-SWITCHING, A PRAGMATIC ANALYSIS - Rustamova Mohinabonu Sherzod qizi (TADQIQOTLAR, 2026)
Abstract: This study investigates how politeness strategies are realized through digital code-switching in bilingual and multilingual online interactions. By analyzing 500 social media posts, instant messaging conversations, and forum discussions, the study identifies patterns in language alternation that reflect social relationships, respect, and identity management. The findings reveal that speakers strategically use code- switching to express positive politeness (solidarity and appreciation), negative politeness (respect and mitigation of imposition), and off-record strategies (indirect communication). Additionally, digital features such as emojis, hashtags, and abbreviations significantly influence the use and interpretation of code-switching. The study highlights the pragmatic importance of digital code-switching and its role in maintaining effective, polite, and socially aware communication in online environments.